Police Oversight of Legality in Railway Freight Transport in Russian Empire During World War I - P. A. Kolpakov (Научный диалог)
This article analyzes the activities of the gendarmerie railway police in ensuring compliance by freight carriers with prohibitions and restrictions on the export of certain raw materials and goods during World War I. Based on documentary materials, it reveals the content of the state policy of the Russian Empire regarding measures to halt the supply of essential resources to the Central Powers’ armies. The study of the administrative documentation of the railway police indicates that particular attention was paid to monitoring freight transport at border stations. The issue of police support for the stable functioning of railways under wartime conditions is explored. Gendarmerie officers facilitated the prioritization of military cargo movement along steel corridors. A critical responsibility of the gendarmerie was uncovering collusion among railway employees and shippers to manipulate train speeds for illicit speculative profit amid commodity shortages. The study concludes that the gendarmerie railway police played a significant role in overseeing the legality of freight transport during World War I. However, amid the disorganization of state mechanisms and deepening crises in Russian society, ensuring uninterrupted and effective railway operations proved impossible.